A Proposed Control Algorithm for Automated Storage and Retrieval System m (ASRS) - R. Hameed, Ali; F. Abdulateef, Osama (Al-Khwarizmi Engineering Journal, 2024)
This paper introduces an algorithm that enhances open-loop stepper motor motion systems. The objective is to close the loop with fewer hardware requirements, increasing flexibility in speed and weight capacity for storage and retrieval (S/R) machines and reducing cost. The method involves integrating the algorithm into a distributed control system, minimizing hardware, processing power, and maintenance shutdowns. The results highlight the algorithm’s effectiveness. Adjusting torque/speed parameters mitigates motor stalling in S/R machines successfully, leading to improved efficiency. Unlike commercial S/R machines, this revolutionizes closed-loop stepper systems, making them more efficient, relatively cost-effective as well as practical for educational purposes.